Effect on myocardial protection techniques on the development of cardiac insufficiency during surgical treatment of ischemic mitral insufficiency - Rudenko, S. A.; Lazorishinetz, V. V.; Rudenko, A. V.; Fedorova, L. S. (Ukrainian Journal of Cardiovascular Surgery, 2017)
To study the effect of different methods of myocardial protection on the development of heart failure in patients with ischemic mitral insufficiency in the early postoperative period analyzed the histories of 142 patients with ischemic mitral insufficiency genesis. The average age of patients at the time of the transaction amounted to 61.8±7.4 years. Hypertension was diagnosed in 59.9% (n=85) of patients with diabetes – at 14.8% (n=21), peripheral artery lesions – at 16.2% (n=23), acute cerebrovascular accident in history – in 3.5% (n=5). The most common complication in the treatment group was acute heart failure (HF) II–III degree, which was diagnosed in 40 (28.2%) operated patients and comprised 71.4% of all complications early pislyaopertsiynoho period. For stabilization in 20 (50%) patients applied IABP. 1 (0.7%) cases after mitral valve was caused by acute heart failure perioperative myocar-dial infarction. Implementation of the method developed by us myocardial protection with additional input solution through grafts has reduced the incidence of heart failure stage II–III in the early postoperative period to 22.1%.